An investigation of semantic similarity judgments about action and non-action verbs in Parkinson's disease: implications for the Embodied Cognition Framework - Kemmerer, David; Miller, Luke; MacPherson, Megan K.; Huber, Jessica; Tranel, Daniel (Frontiers in Human Neuroscience, 2013)
The Embodied Cognition Framework maintains that understanding actions requires motor simulations subserved in part by premotor and primary motor regions. This hypothesis predicts that disturbances to these regions should impair comprehension of action verbs but not non-action verbs. We evaluated the performances of 10 patients with Parkinson’s disease (PD) and 10 normal comparison (NC) participants on a semantic similarity judgment task that included four classes of action verbs and two classes of non-action verbs. The patients were tested both ON and OFF medication. The most salient results involved the accuracies and reaction times (RTs) for the action verbs taken as a whole and the non-action verbs taken as a whole. With respect to accuracies, the patients did not perform significantly worse than the NC participants for either the action verbs or the non-action verbs, regardless of whether they were ON or OFF their medication. And with respect to RTs, although the patients' responses were significantly slower than those of the NC participants for the action verbs, comparable processing delays were also observed for the non-action verbs; moreover, there was again no notable influence of medication. The major dissociation was therefore not between action and non-action verbs, but rather between accuracies (relatively intact) and RTs (relatively delayed). Overall, the data suggest that semantic similarity judgments for both action and non-action verbs are correct but slow in individuals with PD. These results provide new insights about language processing in PD, and they raise important questions about the explanatory scope of the Embodied Cognition Framework.